On the degree of holomorphic mappings from an annulus into an annulus - Nguyen, Doan Tuan; Pham, Viet Duc (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We establish an estimate for the degree of a holomorphic mapping f : K 1 → K 2 (here, K 1 and K 2 are doubly-connected domains) in terms of the modulus of a family of curves in K 2. This estimate generalizes a result obtained by Kobayashi.